Pemberdayaan Ekonomi Masyarakat Melalui Pengolahan Buah Mangrove Nyirih Menjadi Produk Lulur Kecantikan Alami di Desa Sefoyan Kecamatan Simeulue Timur Kabupaten Simeulue - Femi Riza; Nurul Aulia; Ayu Agustina; Sulastri; M. Lahmudin Nor; Treza Desri Winanda; Rini Mastuti; Reffi Aryzegovina; Irmayadi Sastra (Jurnal Cendekia Mengabdi Berinovasi dan Berkarya, 2026)
Sefoyan Village is one of the villages located in the East Simeulue District of Simeulue Regency. Sefoyan Village has a rich mangrove ecosystem, including the presence of the nyirih mangrove tree (Xylocarpus moluccensis). The fruit of this tree is known to contain bioactive compounds that are beneficial for skin care. However, the utilization of nyirih mangrove fruit by the local community remains very limited, so its economic potential has not been fully tapped. Given the existing natural resource potential and the challenges faced, efforts are needed to empower the Sefoyan Village community by utilizing nyirih mangrove fruit to produce natural beauty scrubs. The objectives of this community service activity are to provide education and training to the residents of Sefoyan Village regarding the benefits of nyirih mangrove fruit and the techniques for processing it into natural beauty scrubs, as well as to improve the community’s economy by creating high-value products and to promote economic diversification through the development of nyirih mangrove fruit-based beauty scrubs. The implementation of the activity was carried out through several techniques, including socialization, group discussions, simulations/hands-on practice, and assistance in marketing the processed products. Community empowerment through the utilization of nyirih mangrove fruit (Xilocarpus Moluccensis) into natural beauty scrubs in Sefoyan Village, West Simeulue Subdistrict, Simeulue Regency, Successfully transforming coastal waste into high-value-added products, while opening up new economic opportunities for local residents. Mangrove body scrub products also have promising market prospects, as the trend toward using natural beauty products continues to grow. Herbal and natural products are gaining popularity among the public, thereby creating opportunities for the development of local businesses unique to coastal areas. Community service activities foster greater public awareness of the importance of mangrove ecosystem conservation through sustainable utilization and economic value-added activities.